Effect of the serum 25-hydroxyvitamin D level on risk for short-term residual dizziness after successful repositioning in benign paroxysmal positional vertigo stratified by sex and onset age - Wu, Jing; Jiang, Chun-Yan; Bai, Ying-Xia; Xu, Qian; Sun, Xu-Hong; Pan, Hui; Shu, Liang; Liu, Jian-Ren; Chen, Wei (Frontiers in Neurology, 2023)
Objective A low serum 25-hydroxyvitamin D (25(OH)D) level is relevant to both the occurrence and recurrence of benign paroxysmal positional vertigo (BPPV). However, whether it also contributes to residual dizziness (RD) after successful repositioning maneuvers is unknown. Therefore, this study aimed to explore the correlation between the serum 25(OH)D level and short-term RD severity in patients with BPPV after successful repositioning maneuvers. Methods In total, 251 patients with BPPV after successful repositioning were enrolled and prospectively followed up for 1 week (W1). Serum 25(OH)D values were detected by chemiluminescence immunoassay at enrollment (W0). In addition, we explored the relationship between 25(OH)D values at baseline and RD severity at W1 in different subgroups stratified by sex and onset age (early-onset, ≤50 years; late-onset, >50 years). Results The serum 25(OH)D level of female patients was significantly lower than that of male patients (15.9 ± 6.8 vs. 19.8 ± 6.6 ng/ml, p < 0.001). Its level also decreased in early-onset patients compared to late-onset ones (15.3 ± 5.9 vs. 18.0 ± 7.3 ng/ml, p = 0.003). In addition, early-onset female patients had lower 25(OH)D values than late-onset female patients (14.0 ± 5.5 vs. 17.1 ± 7.2 ng/ml, p = 0.004). However, this difference was not observed between early- and late-onset male patients. Among early-onset female patients, the 25(OH)D values of the moderate-to-severe RD group were lower than those of the minor or no RD group (10.9 ± 3.3 vs. 14.7 ± 5.7 vs. 15.0 ± 5.9 ng/ml, p = 0.046). Multivariate analysis found that decreased 25(OH)D values were related to the occurrence of moderate-to-severe RD in early-onset female patients (OR = 0.801; p = 0.022). This effect did not exist in late-onset female or male patients with BPPV. Conclusions Age and sex differences in serum 25(OH)D levels exist in patients with BPPV. A decreased 25(OH)D level in early-onset female patients may increase the odds of moderate-to-severe RD 1 week after successful repositioning maneuvers.